2019
DOI: 10.1007/s10858-019-00258-0
|View full text |Cite
|
Sign up to set email alerts
|

Tuning a timing device that regulates lateral root development in rice

Abstract: Peptidyl Prolyl Isomerases (PPIases) accelerate cis-trans isomerization of prolyl peptide bonds. In rice, the PPIase LRT2 is essential for lateral root initiation. LRT2 displays in vitro isomerization of a highly conserved W-P peptide bond ( 104 W-P 105 ) in the natural substrate OsIAA11. OsIAA11 is a transcription repressor that, in response to the plant hormone auxin, is targeted to ubiquitinmediated proteasomal degradation via specific recognition of the cis isomer of its 104 W-P 105 peptide bond. OsIAA11 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous studies suggest that the first stage of weight loss is similar to the physical dehydration of starch, while the second stage entailed chemical and thermal degradation. 54 At the third stage, chemical oxidation caused weight loss, which resulted in varied mass losses at temperatures between 300 and 400 °C. This stage, which is a combustion stage, is what completely oxidised the organic materials.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that the first stage of weight loss is similar to the physical dehydration of starch, while the second stage entailed chemical and thermal degradation. 54 At the third stage, chemical oxidation caused weight loss, which resulted in varied mass losses at temperatures between 300 and 400 °C. This stage, which is a combustion stage, is what completely oxidised the organic materials.…”
Section: Resultsmentioning
confidence: 99%
“…Bet et al (2018) reported the 7.8% loss in the first stage is concordant to the native starch, but incorporation of gum has significantly influenced the mass loss. According to prior report, the first stage of weight loss resembled physical dehydration of starch, whereas the second stage involved chemical dehydration as well as thermal decomposition (Acevedo et al, 2019). The second stage weight loss appeared at temperature ranges of 230-350°C, and this loss varied from 40% to 47.42% and 4.31% to 48.41% for variable compositions of SAG and SGG.…”
Section: Thermo-gravimetric Analysismentioning
confidence: 89%